The Effect of Chicken Manure and NPK Mutiara Professional Fertilizer on the Growth and Yield of Katokkon Chili (Capsicum chinensie Jack.) - Gautama, Yudha; Jannah, Noor; Astuti, Puji (Jurnal Agroteknologi dan Kehutanan Tropika, 2025)
Chili is not only used for household consumption as a cooking spice or mixed ingredient in various food and beverage processing industries, but also used for the manufacture of medicines and cosmetics. The purpose of this study was to determine the effect of chicken manure and NPK Mutiara Professional fertilizer and their interactions on katokkon chili plants, to determine the best dosage of chicken manure and NPK Mutiara Professional fertilizer for katokkon chili plant productivity. The study was conducted on February 5-May 2023. The research location is located in Tenggarong sub-district, Kutai Kartanegara Regency, East Kalimantan. The study used an experimental design with a 4 x 3 factorial analysis in a Completely Randomized Design (CRD), with 4 replications. Consisting of 2 treatment factors. Factor I, Chicken Manure Dose (A) consists of 4 levels, namely: without chicken manure or control (a0), fertilizer dose of 125 g/polybag (a1), fertilizer dose of 250 g/polybag (a2), and fertilizer dose of 500 g/polybag (a3). Factor II, Mutiara Professional NPK Fertilizer (M)) consists of 3 levels, namely: without Mutiara Professional NPK fertilizer or control (m0), fertilizer dose of 1.80 g/polybag (m1), and fertilizer dose of 3.60 g/polybag (m2). The results showed that the chicken manure treatment had no significant effect on plant height at 15 days after planting, age at flowering and age at harvest. It had a significant effect on plant height at 30 days after planting. It had a very significant effect on plant height at 45 days after planting and fruit weight per plant. The interaction of treatments had no significant effect on plant height at 15 days after planting, age at flowering and age at harvest.